Forensic Linguistic Analysis: Civil Servant Speech Equating Prostitutes with Probolinggo Parliament Members - Adbaka, Fadhli; Datang, Frans Asisi (Lingua Cultura, 2023)
The research investigated an alleged defamation statement made by a civil servant in Probolinggo, suggesting that the Regional People's Representative Council of Probolinggo (DPRD Probolinggo) held a lower social status than local sex workers, employing forensic linguistics as its analytical framework. The research was a single case study that applied a qualitative approach to analyze the data. A single case study was a suitable method for analyzing a single case of an individual; here was a civil servant in a socialization event attended by the regional government. The data consisted of four sentences of verbal statements and eight accompanying non-verbal cues made by the civil servant toward Probolinggo Parliament members. The research uncovers that the civil servant's remarks contain pointed appraisals and judgments aimed at DPRD Probolinggo members, ultimately leading to legal action predicated on allegations of defaming the collective dignity of DPRD Probolinggo. However, it is important to emphasize that these critical assessments are specific to certain members rather than constituting a comprehensive censure of the entire institutional body. Consequently, the civil servant may potentially be exempt from institutional defamation charges, with these actions interpreted as robust workplace criticisms. Nevertheless, the research underscores the potential legal repercussions stemming from such critiques and the need for a meticulous evaluation of their legal implications within the legal framework, given their potential to generate future legal disputes.